(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
The advancement of industrialization and communications has made man more sensitive and critical, resulting in a variety of health issues. Sedentary lifestyles are becoming more common as a result of the progress of industrialization and communication, resulting in chronic non-communicable diseases such as diabetes, hypertension, cancer, ischemic heart disease, cerebro-vascular accidents, atherosclerosis, varicose veins, and so on. Obesity is a risk factor for several diseases, thus preventing it will reduce the likelihood of developing them. Obesity, like other disorders, is a complex disorder caused by a combination of factors such as food, physical activity, mental health, and overall lifestyle. In Ayurveda, Sthaulya is the closest clinical entity for obesity. Sthoulya’s causality is described in the Asta-Nindita-Purusha chapter. The etiopathogenesis of obesity is caused by an excessive intake of calories combined with a decrease in expenditure. A key weight-loss approach that can be used anywhere to reduce energy density. In Ayurveda, Pathya and Apathya are given specific attention in terms of Ahara, Vihara, and Manasika Entities, so that the ailment can be treated holistically. When these guidelines are followed, the treatment yields a better result in the treatment of the condition. This article attempts to review the pathya and apathy of obesity, as well as discuss the possible causes.